pH, Total Bacteria and Total Fungi Litter Fermentation at Different Ripening Durations - C. S. Utama; B. Sulistiyanto; O. Barus (Universitas Bengkulu, 2021)
This study aims to examine the effect of fermentation time on pH levels, total bacteria and total fungi litter chicken fermented. The research method was carried out by collecting various chicken litters from 16 closed house cages in Semarang City, Demak Regency and Kendal Regency, then combined and fermented. The study used a completely randomized design in the direction of 4 treatments and 4 replications, the treatments were T0 = 0 week litter curing; T1 = 3 weeks litter curing; T2 = 6 weeks of litter curing; T3 = 9 weeks litter curing. The parameters observed were pH value, total bacteria and total litter fungi in broiler chickens. The results showed that there was a significant effect (P <0.05) between curing time on the pH value and the total litter bacteria in fermented broiler chickens. The longer the curing time, the pH value decreases, because the longer fermentation process produces more organic acids. The results of the calculation of total bacteria show that the best treatment is the T2 treatment with the number of bacteria as much as 8.12 x 107 log CFU / g. Meanwhile, the total fungus had no significant effect (P> 0.05) on all treatments. The conclusion of this research is the best chicken litter fermentation at 6 weeks duration of ripening. Produce a total of bacteria and fungi as much as 0.25 x 103 CFU/g and indicated that they were not pathogenic bacteria and fungi.